Philippine white distilled vinegar manufacturing plant using banana fruit a plant design - Alura, Rennie; Ramirez, Jairone; Rina, Luna Mae; De Leon, Rizalinda L.; Ramoso, Patrick D. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Opportunities had risen for possible alternatives for income generating industry for banana other than direct export when China, one of the countrys main markets for banana export, tightened its shore for local products. These available opportunities to establish new local industries for banana open new job opportunities for Filipino as well. With this search for alternative local industry, this plant design proposes the viability of banana as the raw material for the production of white distilled vinegar in the Philippines, not just in terms of process design but also in terms of its profitability. Vinegar has been increasingly popular to consumers through the globe as new blends, uses and specialty products continued to enter the marketplace. Based on the data gathered, there is a growing demand of white distilled vinegar, both locally and internationally, and is the highest among other types of vinegar. Further market data analysis was made in order to determine the forecasted demand of white distilled for the next five year. From the analysis made, the plant proposes to cater about 20% of the forecasted demand as its annual capacity, amounting to 1,073,654.516 kg or 1,071292.316 liters of final product per year. Region XI or Davao region, specifically, Davao del Norte is chosen as to where the plant will be constructed because it has the highest production rate and land area for banana cultivation. It fact, Davao del Norte is considered as the Banana Capital of the Philippines. Process and equipment designs necessary for the implementation of the plant were done based on its capacity, availability of the raw materials including the utilities needed, and of course the necessary condition essential to operate the plant. Basic rules of thumb were employed in the calculation of the dimensions of equipment. Plant layout was done considering safety and practicality. There are hot equipment present in the plant so measures were done with respect to the location of these equipment. Furthermore, since this plant involves food material, stainless steel was chosen as the main type of material to be used in the construction of the equipment since it is the safest. Measures were also taken to avoid contamination of materials will respect to the plant layout. Fermentation is the main process in the production of white distilled vinegar. There are two fermentation vats considered as the major equipment. They both require temperature control systems for optimum production and usage of yeast. Analysis and comparison were done to determine which method is best for both fermentation processes primarily due practical reasons. One of the major equipment in the plant also is the pot still which is used to concentrate the final product. This equipment is only allowed to operate at the limit c of 96°C. It also contains ethanol which is flammable. Therefore, it needs to be monitored to avoid losses and damages caused by fire or explosions. Additionally, a pasteurizer was employed to kill the bacteria present in the final product.Economic study was done to analyze whether the proposed plant is profitable or not. Results show that the Fixed Capital Investment amounts to P109,968,741.6, about 90% of the Total Capital Investment which is P 122,187,490.6. Cash flow analysis was done within 20 year period with consideration on the tax applied being 30% and setting the price of the final product as P45 per liter. Sensitivity analysis on the other hand showed that the profitability of the plant is very sensitive to the investment. An increase in the investment by about 4% already makes the plant unprofitable for 20 years. Internal rate of return is 15.3% which is higher than the MARR (12%), securing the profitability of the plant within 20 year. Payback period is about 12.2 years having the Net Present Worth after 20 years of P 23,804,608.85
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Vinegar; Banana products; Agricultural processing plants -- Philippines